2019
DOI: 10.1021/jacs.9b02909
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Bandgap 2D Silver–Bismuth Iodide Double Perovskite: The Structure-Directing Influence of an Oligothiophene Spacer Cation

Abstract: Three-dimensional (3D) hybrid organic−inorganic lead halide perovskites (HOIPs) feature remarkable optoelectronic properties for solar energy conversion but suffer from longstanding issues of environmental stability and lead toxicity. Associated two-dimensional (2D) analogues are garnering increasing interest due to superior chemical stability, structural diversity, and broader property tunability. Toward lead-free 2D HOIPs, double perovskites (DPs) with mixed-valent dual metals are attractive. Translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
229
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(244 citation statements)
references
References 76 publications
15
229
0
Order By: Relevance
“…The reduced dimensionality of double perovskites also exhibits increased bandgap, which is similar to the results in lead‐based perovskites. Recently, Ag−Bi iodide‐based 2D double perovskites with a reduced direct bandgap of 2.02 eV were reported . Experiments have found that traditional organic groups (BA and related cations) do not form iodine‐based 2D double perovskites.…”
Section: Quaternary Bismuth Halide Of Double Perovskite (A2agbix6)mentioning
confidence: 99%
“…The reduced dimensionality of double perovskites also exhibits increased bandgap, which is similar to the results in lead‐based perovskites. Recently, Ag−Bi iodide‐based 2D double perovskites with a reduced direct bandgap of 2.02 eV were reported . Experiments have found that traditional organic groups (BA and related cations) do not form iodine‐based 2D double perovskites.…”
Section: Quaternary Bismuth Halide Of Double Perovskite (A2agbix6)mentioning
confidence: 99%
“…An iodide-based 2D double perovskite [AE2T]2AgBiI8 (AE2T = 5,5'-diylbis(amino-ethyl)-[2,2'-bithiophene]) has also been recently reported, with an optical band gap of 2.00 eV. 39 Hydrothermal synthesis and structure of the compounds (C6H16N2)2AgBiI8•H2O and (C6H16N2)2CuBiI8•0.5H2O [C6H14N2 = 1,4-cyclohexane-diamine] have also been reported recently. 40 With the aim of evaluating the chemical and structural versatility of hybrid layered double perovskite halides, and to gain insight into structure-property relations, we demonstrate that a large family of cation-ordered hybrid double-perovskite halides can be obtained through the judicious selection of a range of organic and M cations, and halide anions.…”
Section: Introductionmentioning
confidence: 99%
“…3 (n = 3, [47] 4, [28] 5) [48] -L ead-free double perovskites,e ither 3D ones exhibiting direct band gap, [49] or bismuth based 2D ones belonging to the h100i series with n = 2( (butylammonium) 2 CsAgBiBr 7 ), [50] or n = 1( (AE2T) 2 AgBiI 8 ) (AE2T 2+ = 5,5'-diylbis(aminoethyl)-[2,2'-bithiophene]). [51] -l ead-(tin-) and halide-deficient 3D ABX 3 compounds, which can be described from the 3D ABX 3 structure by the substitution process highlighted in this Viewpoint, represent an ew type of promising hybrid perovskites.B esides en 2+ and HEA + cations,longer chain cations have recently stabilized such materials. [52] Ac hallenge in the future will be to predict which organic cations could lead to such materials.T he future will tell us as well if these materials deserve as pecific acronym, and if so,w hich one," hollow perovskites" or "3D d-HPs", will be used.…”
Section: Resultsmentioning
confidence: 99%